HUBUNGAN RELIGIUSITAS ISLAM DAN REGULASI EMOSI MAHASISWA UNTUK TERCAPAINYA SDGS KE-3 - Reskido, Aleea Dian Putri; Shafira Dhaisani Sutra; Irwan Nuryana Kurniawan (Khazanah: Jurnal Mahasiswa, 2024)
Islamic religiosity is a crucial thing to pay attention to, especially for a Muslim. Islamic religiosity plays a role in all aspects of human life, including Muslim college students, who have many roles and are needed to be productive. This study aims to explain the relationship between Islamic religiosity and emotion regulation in Muslim college students in Yogyakarta. This research uses a quantitative approach with a correlational study method. The data collection technique used a purposive sampling technique with participants of 154 Muslim college students in Yogyakarta. This study hypothesizes that there is a positive relationship between Islamic religiosity and emotion regulation in Muslim college students in Yogyakarta. Islamic religiosity was measured using A Psychological Measure of Islamic Religiousness by Abu Raiya et al., and emotion regulation was measured with the Emotion Regulation Questionnaire (ERQ) by Gross & John. The results showed that Islamic religiosity has a positive correlation with emotion regulation. In conclusion, the higher one's Islamic religiosity, the higher one's emotion regulation ability.